Diol-ginsenosides from Korean Red Ginseng delay the development of type 1 diabetes in diabetes-prone biobreeding rats - Chung Ju; Sang-Min Jeon; Hee-Sook Jun; Chang-Kiu Moon (Journal of Ginseng Research, 2020)
Background: The effects of diol-ginsenoside fraction (Diol-GF) and triol-ginsenoside fraction (Triol-GF) from Korean Red Ginseng on the development of type 1 diabetes (T1D) were examined in diabetes-prone biobreeding (DP-BB) rats that spontaneously develop T1D through an autoimmune process. Methods: DP-BB female rats were treated with Diol-GF or Triol-GF daily from the age of 3–4 weeks up to 11–12 weeks (1 mg/g body weight). Results: Diol-GF delayed the onset, and reduced the incidence, of T1D. Islets of Diol-GF–treated DP-BB rats showed significantly lower insulitis and preserved higher plasma and pancreatic insulin levels. Diol-GF failed to change the proportion of lymphocyte subsets such as T cells, natural killer cells, and macrophages in the spleen and blood. Diol-GF had no effect on the ability of DP-BB rat splenocytes to induce diabetes in recipients. Diol-GF and diol-ginsenoside Rb1 significantly decreased tumor necrosis factor α production, whereas diol-ginsenosides Rb1 and Rd decreased interleukin 1β production in RAW264.7 cells. Furthermore, mixed cytokine- and chemical-induced β-cell cytotoxicity was greatly inhibited by Diol-GF and diol-ginsenosides Rc and Rd in RIN5mF cells. However, nitric oxide production in RAW264.7 cells was unaffected by diol-ginsenosides. Conclusion: Diol-GF, but not Triol-GF, significantly delayed the development of insulitis and T1D in DP-BB rats. The antidiabetogenic action of Diol-GF may result from the decrease in cytokine production and increase in β-cell resistance to cytokine/free radical–induced cytotoxicity.